تأثير أساليب التدريس لحماسة الطلاب في تعلم اللغة العربية لدى طلاب الفصل الحادى عشر لقسم اللغة في مدرسة دار التقوى الثانوية الإسلامية سينجونانجونج بورواساري باسوروان - Titin Khoirun Nisa' (Universitas Yudharta Pasuruan, 2017)
Arabic language learning model is a way of being selected and used by a teacher in delivering material to facilitate Arabic students in accepting and understanding the Arabic language material. As an explanation of the learning model function above, researchers want to know whether the model of learning the Arabic language has an impact on students ' motivation in learning Arabic. The research method used is descriptive quantitative. While the collection of data using the techniques of observation and interviews. The source of the data from this study is the student motivation questionnaire. Data analysis is a statistical analysis. From the questionnaires that have been scattered in language classes consisting of 6 statements about the learning model and 14 statement about the motivation of students. It can be shown the results of skoring of Class XI language 2 (experimental classes) reached 1435 or 71.75, and XI language 1 (grade control) reaches 1241 or 60.80. Based on the research results then can be inferred that there was influence of learning motivation of students against the model in studying Arabic.